Inquiry-based learning: strategies and benefits (Journal of Educational Sciences, 2021)
This article is concerned with the notion of inquiry-based learning, its strategies of implementa- tion and benefits in the classroom. It discusses the foundational components of inquiry-based learning. Inquiry is a multifarious activity that templates learners to inquire or bring constructive questions that lead to the relevant answers. In inquiry learning learners are presented how knowledge is generated and expressed and how they can gain the knowledge and abilities necessary to become life-long learners. The general theoretical methods of research such as analyses, synthesis were conducted. The paper of- fers the theory review of strategies, benefits, the efficacy and nature of inquiry-based learning to educa- tion that seek to involve learners in this approach, knowledge creation and authentic intellectual work. Definitional understandings of involving learners in inquiry-based learning and knowledge creation were identified in wide range. Analyses revealed various teaching strategies, differing with regard to direction and different perspectives and outcomes of regulation.The definitions, strategies and benefits of inquiry-based learning which were identified as the most powerfull ones during the process of the research can be used as theoretical didactic tool in the meth- odology of teaching.Key words: inquiry-based learning, problem-based learning, strategy, benefits, request, research.